Prevention of the Emerging COVID-19 Infection in Dialysis Centers - Mohkam, Masoumeh; Kompani, Farshid (Journal of Pediatric Nephrology, 2020)
COVID-19, a disorder caused by a novel coronavirus, is a major global human threat. Patients with end stage renal disease and those undergoing dialysis constitute a susceptible population because of their less efficient immune system. Hemodialysis wards are considered as a high-risk area in the outbreak of a COVID-19 epidemic, therefore prevention plays a key role which is essential in the mitigation and containment of the COVID-19 outbreak in hemodialysis centers. We try to classify prevention guidelines concisely in this article for easier implementation. Keywords: COVID-19; Nephropathy; Dialysis; Prevention.